What do empirical findings reveal about modelled energy demand and energy ratings? Comparisons of gas consumption across the English residential sector. (June 2019) - Summerfield, A.J.; Oreszczyn, T.; Palmer, J.; Hamilton, I.G.; Li, F.G.N.; Crawley, J.; Lowe, R.J.
Abstract: Energy ratings and national housing energy models are useful for energy policy evaluation and development, but limited empirical validation of energy demand estimates is available across residential sub-sectors. This study used data from a sample of over 2.5 million gas-heated dwellings in England from the National Energy Efficiency Data-Framework (NEED) to compare with estimates of 2012 gas consumption from the Cambridge Housing Model (CHM), a national energy stock model. The analysis quantified differences by dwelling type, size, and age band. It also compared variations in gas consumption from NEED dwellings with that expected from Energy Performance Certificate (EPC) bands. The findings show that the CHM overestimates average gas consumption from NEED for all dwelling types built before 1930, most notably for large detached dwellings. For other dwellings built since 1930, the model estimates were in relatively close agreement with NEED data. Furthermore, a simple comparison between estimated gas consumption and NEED data suggests savings from upgrading dwellings to at least EPC band C would be substantially lower than expected. Findings raise question regarding assumptions used in models and EPC ratings, including occupancy and space heating patterns, and have implications for development of energy models and policy regarding energy efficiency programmes. Highlights: Residential energy policy development relies on models and national statistics. Energy models and ratings for dwellings need to be compared with empirical data. Models tend to overestimate gas consumption, notably older larger detached dwellings. Mean gas consumption of dwellings with poor energy ratings is lower than expected. Targeted retrofit initiatives may result in much lower gas savings than expected.